The Irish Prison System - Trinity FLAC; Murphy, Mary (Trinity Free Legal Advice Centre, 2018)
This research project was conducted by Trinity FLAC with help from Professor Mary Rogan. It examines how the integrity and well-being of prisoners is balanced against financial or administrative concerns. While its analysis is primarily legal, the report shall also consider the cultural and political realities that helped to shape law and policy.
Keywords: Legal advice; Prison; Prisoner well-being; Ireland